Synthesis, structure, and electrochemistry of Ag-modified LiMn2O4 cathode materials for lithium-ion batteries - Tay, S.F.; Johan, M.R. (Springer Verlag (Germany), 2010)
The composite of silver-modified lithium manganese oxide were prepared using thermal decomposition method of different mole ratio Structural characterization was carried out by X-ray diffraction (XRD) XRD analysis revealed different patterns as the content of the dopant in the spinel increases Phase analysis shows that Ag particles were dispersed on the LiMn2O4 surface instead of entering the spinel structure On the other hand, the electrochemical behavior of cathode powder was examined by using two-electrode test cells consisting of a cathode, metallic lithium as anode, and a solid polymer electrolyte of 0 87PEO-0 13LiCF(3)SO(3)-0 10DBP According to the electrochemical tests results, the influence of the Ag additive content on the electrochemical properties of Ag/LiMn2O4 composites is clearly shown